Analisis profitabilitas bank syariah sebelum dan selama pandemi covid-19 (studi kasus pada PT Bank Muamalat Indonesia TBK) - Atif Windawati; Andi Nursyamsi Amin; Alvianita Gunawan Putri; Iwan Budiyono (Journal of Applied Business Administration, 2022)
The Covid-19 pandemic has impacted many sectors including the Islamic Banking sector. This study aims to analyze the profitability of Islamic banking before and during the Covid-19 pandemic, a case study at Bank Muamalat Indonesia (BMI). The research indicators used are banking financial ratios in the form of ROA (Return on Assets), ROE (Return on Equity), BOPO (Operating Agency to Operating Income), NOM (Net Operating Margin), and EPS (Earning Per Share). The research method used is a comparative study with a quantitative approach using data from Quarter I to IV financial statements for 2019 - 2020. The results show that there is no significant difference in the profitability of BMI before and during the Covid-19 pandemic seen from ROA, ROE, BOPO, NOM, and EPS.